Effect of rotation of feed and seed rods on the quality of Na0.75CoO2 single crystal grown by traveling solvent floating zone method - Sekar, C.; Paulraj, S.; Kanchana, P.; Schüpp-Niewa, B.; Klingeler, Rüdiger; Krabbes, G.; Büchner, B. (Materials research bulletin, 2011)
High purity Na0.75CoO2 single crystals have been grown by floating zone method. We found the rotation of feed and seed rods play a crucial role in growing high quality single crystal. Systematic investigations suggest the occurrence of a phase separation at microscopic level, such as the separation into Na-rich and Na-poor domains during the growth, and formation of impurity phase(s) depending on growth conditions. NaxCoO2 (x=0.30, 0.60) crystals have been prepared by sodium deintercalation from Na0.75CoO2. Powder X-ray and energy dispersive X-ray analyses have confirmed the phase purity and homogeneity of the samples. Magnetic susceptibility measurements of x=0.60 and 0.75 crystals indicate a bulk phase transition at 22K and an anomaly around 339K and 334K respectively which are attributed to structural transition. In addition some unique features related to Na0.60CoO2 were observed.